Clinical Microwave Tomographic Imaging of the Calcaneus: A First-in-Human Case Study of Two Subjects - Meaney, Paul M.; Goodwin, Douglas; Golnabi, Amir H.; Zhou, Tian; Pallone, Matthew; Geimer, Shireen D.; Burke, Gregory; Paulsen, Keith D. (IEEE transactions on biomedical engineering, 2012)
We have acquired 2-D and 3-D microwave tomographic images of the calcaneus bones of two patients to assess correlation of the microwave properties with X-ray density measures. The two volunteers were selected because each had one leg immobilized for at least six weeks during recovery from a lower leg injury. A soft-prior regularization technique was incorporated with the microwave imaging to quantitatively assess the bulk dielectric properties within the bone region. Good correlation was observed between both permittivity and conductivity and the computed tomography-derived density measures. These results represent the first clinical examples of microwave images of the calcaneus and some of the first 3-D tomographic images of any anatomical site in the living human.